2010 IEEE Network Operations and Management Symposium - NOMS 2010 2010
DOI: 10.1109/noms.2010.5488365
|View full text |Cite
|
Sign up to set email alerts
|

Service creation and execution with the Service Refinement Cycle

Abstract: Service composition is today mostly a manual process and automated service creation techniques are not ready for prime time in IT and network system development. This paper presents the Service Refinement Cycle as an integrated framework for dealing with the service lifecycle composed of stages like service creation, deployment, execution and management. The main realization of the cycle is the Service Code, which contains executable specifications (code) that may run at any compatible engine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The service refinement cycle SRC [1], which is a result of the service refinement approach, is an integrated abstract framework for dealing with the service life cycle, which defines a common 'language' (or structure) for specifying and understanding service composition. It is composed of a sequence of phases (service, process, policy, and binding), as depicted in Figure 2, where each phase adds some features for enhancing the capacity of services to adapt their behavior, according to different requirements.…”
Section: Service Refinement Cycle and Service Codementioning
confidence: 99%
See 1 more Smart Citation
“…The service refinement cycle SRC [1], which is a result of the service refinement approach, is an integrated abstract framework for dealing with the service life cycle, which defines a common 'language' (or structure) for specifying and understanding service composition. It is composed of a sequence of phases (service, process, policy, and binding), as depicted in Figure 2, where each phase adds some features for enhancing the capacity of services to adapt their behavior, according to different requirements.…”
Section: Service Refinement Cycle and Service Codementioning
confidence: 99%
“…We developed two versions of a service creation tool with different levels of automation based on an underlying framework called service refinement cycle (SRC), and both use the service code [1] to describe the final executable service. We found that by increasing the level of automation, we could significantly improve the functioning of the activities related to service creation, in terms of both human effort and the expressiveness of the solution.…”
Section: Introductionmentioning
confidence: 99%